Cells of the human respiratory tract support the replication of pathogenic Old World orthohantavirus Puumala - Hägele, Stefan; Nußhag, Christian; Müller, Alexander; Baumann, Alexandra; Zeier, Martin; Krautkrämer, Ellen (Virology journal, 2021)
Transmission of all known pathogenic orthohantaviruses (family Hantaviridae) usually occurs via inhalation of aerosols contaminated with viral particles derived from infected rodents and organ manifestation of infections is characterized by lung and kidney involvement. Orthohantaviruses found in Eurasia cause hemorrhagic fever with renal syndrome (HFRS) and New World orthohantaviruses cause hantavirus cardiopulmonary syndrome (HCPS). However, cases of infection with Old World orthohantaviruses with severe pulmonary manifestations have also been observed. Therefore, human airway cells may represent initial targets for orthohantavirus infection and may also play a role in the pathogenesis of infections with Eurasian orthohantaviruses.
Gesehen am 28.09.2021